The Role of Teacher Competence in the Economic Learning Process at MA Muhammadiyah Kadudampit - Aulia Nurul Janah; Agus Susilo (Journal La Sociale, 2023)
The problem of teacher competence is still often encountered, teachers are not ready to apply innovative teaching methods and tend to return to lecture-based learning patterns, teacher qualification and certification improvement programs have no direct impact on improving student achievement, teachers are trapped in bureaucratic thinking to implement the curriculum, encouragement and willingness to learn and develop are not prioritized by teachers. As a result, when learning takes place some students are daydreaming, students with high intellectual abilities tend to be passive, while students with low intellectual abilities tend to be active and even disruptive which causes them to learn less smoothly, the learning process will again focus on the teacher who must be a guide, and when the teacher explains the material they feel they are often seen busy themselves, ignorant and some even fall asleep. The purpose of this study was to determine the condition and role of teacher competence in the learning process of economic subjects at MA Muhammadiyah Kadudampit, Sukabumi, West Java. The research conducted was qualitative research with a case study design. Data validity was done by triangulating data sources and triangulating methods. Data analysis used by researchers is an interactive model including data collection, data reduction, data presentation, and concluding data results. Based on the results of observations of teacher competence at MA Muhammadiyah Kadudampit, Sukabumi, West Java has not fully met the four competencies that a teacher must have, including: pedagogical, personality, social, and professional competencies.